On-farm nitrogen, phosphorus, and potassium partial balances in three major rice production systems in sub-Saharan Africa - Rakotoson, Tovohery; Johnson, Jean-Martial; Senthilkumar, Kalimuthu; Ibrahim, Ali; Saito, Kazuki (Elsevier, 2025)
Abstract Context Quantifying nutrient balances in cropping systems is critical for better nutrient management towards efficient and sustainable agriculture. However, information about nutrient balances for rice in major production systems is limited in sub-Saharan Africa (SSA). Objectives This study aimed to assess nitrogen (N), phosphorus (P), and potassium (K) balances in the three major rice production systems in SSA and their relationships with rice yield at different spatial levels. Methods On-farm survey of 1025 farmers’ fields in 32 sites within 19 countries across West, Central, and East Africa, and for three major rice production systems consisting of irrigated lowland, rainfed lowland, and rainfed upland were used to quantify the nutrient partial balances calculated as nutrient inputs minus outputs. Results The study found significant variations in N, P, and K partial balances across regions, countries, and production systems ranging from −209–220 kg ha−1 for N, −39–86 kg ha−1 for P, and −282–163 kg ha−1 for K. Production system was the main source of these variations, while region largely contributed to the P partial balance. The partial balance of all three nutrients was generally negative except for a few sites, with more negative P (70 %) and K (73 %) partial balances compared to the N partial balance (51 %). East Africa had the largest negative partial balances, except for Uganda. Rainfed upland rice was the least sustainable, with negative partial balances of 13, 1, and 13 kg ha−1 for N, P, and K, respectively. There were inconsistent relationships between grain yield and partial nutrient balance. Conclusions N, P, and K partial balances in rice production in SSA largely vary and are mostly outside of acceptable ranges. Irrigated lowland rice is the most sustainable. We identified clusters of combinations of sites and production systems based on yield and nutrient partial balance and suggested research and development strategies for improving yields and optimizing nutrient balances. Implications For comprehensive nutrient balance assessment, future studies should take into account variations in residue management, biological N fixation in lowland rice systems, and organic input.